Implementation of Aggloromative Hierarchical Clustering Using Single Linkage - Dr. G. Vijaya Lakshmi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Classifying and grouping similar type of data objects in one segment is known as clustering. There are different types of techniques to create the clusters namely partitioning methods, hierarchical methods, density-based methods, and grid-based methods. . In this paper, we focus on agglomerative hierarchical techniques which is also known as bottom-up approach. In this approach the objects are successively form clusters into one until termination condition holds. In this paper, python we construct distance matrix by measuring the distance between the two data points. There after a dendrogram is prepared by providing a visual representation that helps to the find the optimal number of clusters.